The American Elections as context for the Game Theory application in strategic political marketing - Markaki, Evangelia; Chadjipantelis, Theodore (Τετράδια Ανάλυσης Δεδομένων, 2024)
The American Elections attract always the interest of political marketing science. As elections they have been innovative with great appeal and their influence has a global perspective. The Game theory approach in political marketing inaugurates a new strategic prospect for the political competition. It combines and evaluates different political marketing strategies and show how they can affect the elections’ result. Game theory combines the models of conflict and cooperation for people whose decision-making is considered rational. We consider the political competition as a strategic game, where we have to identify the opposing players, the strategies used during the game and its rules. Using the game theory and the political marketing approach, our study examines the different strategies that politicians used during the American election of 2016, explaining how their strategy influences the result of the elections. We investigated mostly which approach on financial, social and environmental issues, security issues, immigration and international relations has the best results for the political parties. We measure the intensity of the candidates’ focus on these issues and we present game theory matrixes as examples to this innovative conceptual framework. This study presents a new conceptual approach that can be used for strategic political marketing design and campaigns.